Inciding Factors in the Academic Performance in First Year Students at the University of Cuenca, Ecuador - Verdugo Guamán, María Eugenia (2023)
A sequential mixed study was applied to identify factors inherent to teachers and college students that influence academic performance and recognize some expectations about high school graduates who enter university. We worked with the performance results of the first semester of 1314 students from the University of Cuenca. An interview or focus group was conducted with 24 students, 25 high school teachers, 33 college professors, and five experts. We worked with a performance matrix classified according to the types of establishment, age, and gender of the students. The qualitative analysis was made with questionnaires validated by experts and adapted to each educational actor. The results allowed us to identify better performance among students from private education than public education. The female gender performs better than the male gender, and there are no differences according to age. Among the factors of teachers, their pedagogical and didactic profile stands out as a condition for obtaining better performance. Finally, the university has expectations of new students with critical thinking, reading comprehension, logical-mathematical ability, and research capacity.